Influence of Partner Type on Acceptability and Likelihood of Use of a Rectal Microbicide Among Young Men Who Have Sex With Men in the United States and Puerto Rico. Issue 6 (23rd July 2016) - Giguere, Rebecca; Dolezal, Curtis; Bauermeister, José A.; Frasca, Timothy; Valladares, Juan; Febo, Irma; Cranston, Ross D.; Mayer, Kenneth; McGowan, Ian; Carballo-Diéguez, Alex
Abstract : This study examined how acceptability of placebo gel with receptive anal intercourse (RAI) and likelihood of future rectal microbicide use varied across partner types. Because no rectal microbicide is available yet, use of placebo permitted the study of gel use behavior in real-life circumstances. A total of 87 men who have sex with men (MSM) aged 18 to 30 years inserted placebo gel rectally before RAI during 12 weeks. Using mixed-methods design, participants completed a behavioral questionnaire and in-depth interview. In all, 62 men (71.3%) reported gel use with a lover (i.e., spouse equivalent, boyfriend), 32 (36.8%) with a one-night stand (i.e., man with whom you had sex once), and 29 (33.3%) with an "other" male partner. While gel acceptability was high across partner types, use with lovers was facilitated by trust and familiarity; yet trust made participants believe protection was less necessary. Conversely, participants expressed high likelihood of using gel with one-night stands, whom they perceived as riskier; yet they felt less comfortable discussing gel with them, often resorting to covert use or forgoing gel. A successful microbicide will be positioned as a sexual pleasure enhancer so that men can present it to their lovers and other partners as a gel that improves sex and secondarily prevents human immunodeficiency virus (HIV).